SEORANG PENDERITA CALCIPHYLAXIS PADA GAGAL GINJAL KRONIK - -, Arvanita; SL, Jodi (journal of internal medicine; Vol. 12, No. 1 Januari 2011, 2012)
Calciphylaxis, also called calciÞ c uremic arteriolopathy, is a rare abnormality which characterized by medial calciÞ cation of the small arteries and ischemia of the subcutaneous tissue, often leading to necrosis of subcutaneous fat and skin. It affects mainly woman with ESRD.  A 48 year old woman with ESRD had a history of long standing ESRD which was being treated by hemodialysis for 13 years and peritoneal dialysis for 12 months. Two weeks prior to admission, she complained of a constant dull aching pain accompanied by multiple cutaneous ulcers on both distal extremities. The symptoms did not resolve with antibiotic and analgesic treatment. The skin of the leg had multiple violaceous lesions which were tender on palpation. There was multiple painful lesions with diameter 6 ! 8 cm, necrotic ulcerated lesions surround by erythema. Laboratory data revealed serum calcium was 10.4 mg/dl, phosphate was 8.5 mg/dl and parathyroid hormone level 2,164. Plain Photo of abdomen and both extremity revealed calciÞ cation soft tissue. Skin biopsy was consistent of CalciÞ c Uremic Arteriolopathy (CUA). Histopathology studies showed metastatic calciÞ cation sub cutis (cutaneous calciphylaxis) and arteriolosclerosis within superÞ cial dermis. The patients was treated with local wound care, fosrenol 3 x 500 mg and usual treatment for CKD were continued.  Response calciphylaxis after the treatment was getting bette
Keywords: cutaneous, calciphylaxis, CKD